The ability to claim financial losses for the person who has vegetative life with comparative study - Abbas Mirshekari; Fateme sadat Hosseini (پژوهش‌نامه حقوق اسلامی, 2020)
Today, The Personal injuries are more important because of their effects on the body and soul of man and Also their Complex dimensions they have found. There are numerous difficulties about this subject and the assessment and compensation of personal injuries for the people who are in vegetative life, is one of them. These Damaged persons, on one hand are live, because they can breath normally and totally the involuntary body activities are done by it self. On the other hand, they don’t have any cognitive activities and they don’t have awareness about the environment. This research wants to study about the compensation of financial damages for these persons who are in mentioned condition. We should pay attention that their live is non-deployed and this has special effect. Any way it looks like that medical expenses and the cost of living can be asked and Also, The loss of income, but with special attention about their condition.